2014
DOI: 10.1177/230949901402200109
|View full text |Cite
|
Sign up to set email alerts
|

Negative-Pressure Wound Therapy over Surgically Closed Wounds in Open Fractures

Abstract: Purpose. To evaluate the outcome of open fracture surgery with negative-pressure wound therapy (NPWT) applied directly over surgical wounds. Methods. Medical records of 10 men and 4 women aged 6 to 70 (mean, 43.7) years who underwent internal fixation, external fixation, or splint application for open fractures of the lower leg (n=7), foot and ankle (n=5), or knee (n=2), and NPWT were reviewed. The NPWT was applied directly over the surgical wound without a non-adherent contact layer. The foam was changed ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
0
28
0
1
Order By: Relevance
“…This therapy can promote granulation tissue formation and improve wound healing through reducing tissue edema, removing factors that inhibit wound healing, increasing wound perfusion, and reducing incidence of infection [5][8]. However, controversy still remains regarding the benefits of NPWT on bone tissue, though there have been many clinic and basement reports about its application in treatment of open fracture or osseous defect combined with soft tissue injury, and these studies nearly all show that NPWT can effectively improve wound and bone healing or has no deleterious effect on fracture healing [9]–[12].…”
Section: Introductionmentioning
confidence: 99%
“…This therapy can promote granulation tissue formation and improve wound healing through reducing tissue edema, removing factors that inhibit wound healing, increasing wound perfusion, and reducing incidence of infection [5][8]. However, controversy still remains regarding the benefits of NPWT on bone tissue, though there have been many clinic and basement reports about its application in treatment of open fracture or osseous defect combined with soft tissue injury, and these studies nearly all show that NPWT can effectively improve wound and bone healing or has no deleterious effect on fracture healing [9]–[12].…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate whether NPWT could promote osteogenic differentiation of MDSCs in vitro, we examined the expression of osteogenic markers. Related articles showed that NPWT could promote the healing of open fractures in clinical and experimental studies [9,26]. In our previous research, we also found that NPWT could promote MSC osteogenic differentiation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when the VAC system is used on a closed wound, it is recommended that an additional nonadhesive wound contact layer be placed between the foam dressing and the skin to avoid direct contact. 3,35 We believe that our lack of local skin complications is due to the PICO system, which is uniquely designed to be a skin-friendly device placed over closed surgical incisions using a multilayer silicone dressing. 13 Hudson et al 13 reported that there was neither skin damage nor maceration to healthy skin by the application of negative pressure in the form of the PICO system and neither pain nor trauma to the wound on dressing removal.…”
Section: Discussionmentioning
confidence: 99%